2020
DOI: 10.3389/fpsyg.2020.00398
|View full text |Cite
|
Sign up to set email alerts
|

No Need to Worry? Anxiety and Coping in the Entrepreneurship Process

Abstract: Understanding experiences of and responses to anxiety is foundational to developing robust theories of entrepreneurial behavior. Using open-ended, vignette and graphical elicitation interviews with 77 entrepreneurs, we inductively investigate the experience of and coping responses to anxiety during the entrepreneurship process. We develop a comprehensive and dynamic goal-striving model to explain experiencing and coping with entrepreneurial anxiety by integrating empirical findings with appraisal and control t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 70 publications
2
40
1
Order By: Relevance
“…Thus, in order to understand what fosters or restrains business venture activities, it is necessary to understand these antecedents and how they influence individuals' perception, attitude and intention associated with the creation of a business organization (Krueger et al, 2000). Previous studies found that the entrepreneurial process is affected by risky, uncertain and crisis conditions (Keh et al, 2002), such as a macroeconomic crisis or a war (Amorós et al, 2019), and mental disorders (Gorgievski et al, 2010;Thompson et al, 2020). However, what is less known are the impacts of the fear and anxiety of Covid-19 on the entrepreneurial process, while others have shown that the Covid-19 pandemic is determined as a major shock affecting entrepreneurship in general (e.g.…”
Section: The Effect Of the Fear And Anxiety Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in order to understand what fosters or restrains business venture activities, it is necessary to understand these antecedents and how they influence individuals' perception, attitude and intention associated with the creation of a business organization (Krueger et al, 2000). Previous studies found that the entrepreneurial process is affected by risky, uncertain and crisis conditions (Keh et al, 2002), such as a macroeconomic crisis or a war (Amorós et al, 2019), and mental disorders (Gorgievski et al, 2010;Thompson et al, 2020). However, what is less known are the impacts of the fear and anxiety of Covid-19 on the entrepreneurial process, while others have shown that the Covid-19 pandemic is determined as a major shock affecting entrepreneurship in general (e.g.…”
Section: The Effect Of the Fear And Anxiety Of Covid-19mentioning
confidence: 99%
“…Over the last two decades, scholars have growingly investigated the psychological factors of nascent entrepreneurs to have better understanding of mechanisms underlying the influence of these psychological problems on entrepreneurial activities (Gorgievski et al, 2010). Nevertheless, almost all previous studies either examine the relationship between psychological disorders, such as psychiatric symptoms (Leung et al, 2020) and Attention-Deficit Hyperactivity Disorder symptoms (Yu et al, 2019), and entrepreneurship, or focus on exploring psychological distress, such as stress and anxiety about financial problems (Gorgievski et al, 2010), or general anxiety (Thompson et al, 2020) and business venture. However, there is a dearth of literature found to explore the fear and anxiety of Covid-19 on entrepreneurial activities (Hernández-Sánchez et al, 2020), while this information is really important and necessary for both scholars and practitioners (Giones et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The uncertainties, challenges, and stressors that come with the entrepreneurial process often generate significant and recurrent fear of failure (Cacciotti et al, 2016; Kollmann et al, 2017; Thompson et al, 2019). There are three main reasons why this is important, and the seminal work by Cacciotti et al (2016) provides empirical evidence for all three.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Therefore, the hypothesis according to which fear of failure has a negative effect on entrepreneurial intentions was validated (H1). Engel et al [49] and Thomson et al [50] obtained similar results, showing that fear of failure affects entrepreneurs' well-being and their ability to act.…”
Section: Discussionmentioning
confidence: 74%
“…Engel et al [49] noted that fear of failure affects entrepreneurs' well-being and their ability to act. However, there is also the possibility that entrepreneurs' anxiety helps them achieve the required goals and standards, fear of failure being the result of anxiety and an accumulation of positive and negative emotions [50]. Fear of failure is activated by obstacles which appear in the period specific to the entrepreneurial activity start-up, as shown by Kollmann et al [51], namely resource-based, market-based, and capital-based.…”
Section: Fear Of Failurementioning
confidence: 99%